Dickens and creativity - Hardy, Barbara Nathan (Continuum literary studies., 2008)
This monograph covers Dickens and creativity, analysing both his discussion of creativity and imagination and illustrations in his work. Charles Dickens' experience and imagining of creativity is at the heart of his self-awareness, subject-matter and narrative. His intelligence works intuitively rather than conceptually and ideas about imagination often emerge informally in personal letters and implicitly through characters, language and story. His self-analysis and reflexive tendency are embedded in his styles and forms of narrative and dialogue, images of normality, madness, extremity, subver.